Employee lawsuits and business downsizing: Evidence from labor unions - Unsal, Omer (Journal of Financial Stability, 2024)
In this paper, we examine how employee lawsuits are related to firms’ business decisions. By using union-filed lawsuit data, we document that litigation increases the likelihood of firms downsizing their businesses. Furthermore, cases filed by unions lead to an increase in both the number of store closures and the number of employees affected by these closures. We demonstrate that violations related to labor have a significant negative impact on operating performance. Our findings reveal the fact that the cost of labor, damage to reputation, legal liabilities, and diverted resources resulting from litigation damages firms’ new business opportunities. Overall, our results highlight the importance of employee treatment at the workplace, which affects corporate decisions.